A Narrative Literature Review Considering the Development and Implementation of Longitudinal Integrated Clerkships, Including a Practical Guide for Application. (May 2019) - Brown, Megan EL; Anderson, Kevin; Finn, Gabrielle M
Hailed by supporters as the answer to many challenges facing medical schools and the wider health care system, longitudinal integrated clerkships (LICs) offer a practical and sustainable alternative to more traditional block rotational models. Given this, their popularity as a curricular measure is increasing, although such clerkships remain relatively novel within the United Kingdom. This narrative literature review of international work provides a comprehensive introduction to developing and implementing LICs within medical education. This review generates a practical guide for medical educators with a focus on the development and implementation of LICs within the United Kingdom, on which there is little work. Using illustrated examples and with reference to contemporary literature, it outlines the rationale for considering an LIC within a curriculum, the different types of LIC, barriers and enabling factors to LIC implementation and considers the contemporary application of LIC models within the United Kingdom. The practical guide details key questions educators must consider when developing and implementing an LIC, particularly within the landscape of UK medical education.